Rivaroxaban Modulates TLR4/Myd88/NF-Kβ Signaling Pathway in a Dose-Dependent Manner With Suppression of Oxidative Stress and Inflammation in an Experimental Model of Depression - Abdelzaher, Walaa Yehia; Mohammed, Hanaa H.; Welson, Nermeen N.; Batiha, Gaber El-Saber; Baty, Roua S.; Abdel-Aziz, Asmaa Mohamed (Frontiers in Pharmacology, 2021)
Depression is a common mental illness leading to upset or anxiety, with a high incidence rate in the world. Depression can lead to suicidal thoughts and behavior. The present study aimed to evaluate the effect of the direct oral anticoagulant rivaroxaban (RVX), in the model of depression induced by chronic unpredicted mild stress (CUMS) in rats. Fifty-six male Wister rats randomly divided into 7 experimental groups(8 rats/ group); Group 1: Control group given vehicle per oral (p.o.), Group 2: RVXL- control group (received rivaroxaban 20 mg/kg /day, p.o.), Group 3: RVXH- control group (received rivaroxaban 30 mg/kg /day, p.o.), Group 4: Chronic unpredictable mild stress (CUMS) group, Group 5: FLX-treated CUMS group (received fluoxetine 10 mg/kg/day, p.o.), Group 6: RVXL- treated CUMS group (received rivaroxaban 20 mg/kg /day, p.o.), Group 7: RVXH- treated CUMS group (received rivaroxaban 30 mg/kg /day, p.o.), the rats received the drugs from the first day of the experiment and continued till 4 weeks; the duration of the study. The followings were measured: monoamine neurotransmitters, malondialdehyde (MDA), total nitrite/nitrate (NOx), reduced glutathione (GSH), superoxide dismutase (SOD), Toll-like receptor 4 (TLR4), myeloid differentiation factor 88 (MyD88), nuclear factor‐kappa B (NF‐κB), tumor necrosis factor-α (TNF-α), brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor-A (VEGF-A). A forced swimming test (FST) was done. Furthermore; histological changes, glial fibrillary acidic protein (GFAP) immuno-expression were evaluated. CUMS showed a significant decrease in hypothalamic neurotransmitters, hippocampal GSH, SOD, BNDF, VEGF-A with a significant increase in hippocampal MDA, NOx, NF-kβ, Myd88, TLR4, TNF-α, and GFAP immuno-expression. RVX showed significant improvement in all parameters (p-value < 0.0001). In conclusion, RVX in a dose-dependent manner possesses potent ameliorative effects against depression by reducing the oxidative stress and inflammatory process, through the regulation of the TLR4/Myd88/NF-kβ signaling pathway.